Phase change capsule with toughened shell and preparation method of phase change capsule
By introducing polyvinyl alcohol into the calcium alginate shell and preparing phase change capsules through microfluidic control technology to form crosslinked crystals, the problem of insufficient mechanical properties of the existing phase change capsule shell is solved, and the compression strength and toughness are significantly improved, and the service life is extended.
Patent Information
- Application Number
- CN202411661252.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The mechanical properties of existing phase change capsule shells are poor, resulting in defects such as core material leakage and short service life, especially the insufficient strength and reliability of calcium alginate shells.
Phase change capsules are prepared using microfluidic control technology, and polyvinyl alcohol is introduced into the calcium alginate shell. The crosslinking crystals of polyvinyl alcohol and calcium alginate are formed by repeatedly freezing and thawing, thereby enhancing the crosslinking and tightness of the shell.
The compression strength and toughness of phase change capsules are significantly improved. Compared with conventional calcium alginate shells, the compression strength is enhanced by 20.5 times and the toughness is improved by 31.18 times, extending the service life of phase change capsules.
Smart Images

Figure CN119529769A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite material preparation, and in particular to a phase change capsule with a toughened shell and a preparation method thereof. Background Art
[0002] Phase change capsule is a phase change energy storage material with a typical core-shell structure, which uses organic material, inorganic material or organic-inorganic composite material as the shell and phase change material as the core material. Due to the protective effect of the shell on the internal phase change material, it can effectively prevent the leakage, evaporation and oxidation of the phase change material, and improve the thermal stability and service life of the phase change material. It can be seen that a stable, reliable and durable shell is a necessary prerequisite for achieving long-term and effective encapsulation of the core material inside the phase change capsule.
[0003] However, at present, during the encapsulation process of phase change materials, the preparation of shells often faces problems such as poor controllability and low encapsulation success rate. In particular, many phase change capsule shells have poor mechanical properties and poor reliability, which often leads to defects such as core material leakage and short service life in actual applications. Taking the calcium alginate shell commonly used in microfluidic preparation of phase change capsule technology as an example, although this material has the advantages of low cost, high curing efficiency, and environmental friendliness, the calcium alginate shell has poor strength and is prone to deformation or even rupture during actual application, which seriously restricts the reliability, stability and service life of the phase change capsule.
[0004] Therefore, for commonly used phase change capsule shell materials such as calcium alginate but with poor mechanical properties, research on strengthening their mechanical properties is carried out, and then a preparation method for phase change capsules with toughened shells is developed. This has important practical significance for improving the reliability, stability and service life of phase change capsules in practical applications and expanding their application areas. Summary of the invention
[0005] Technical problem to be solved: In view of the problems existing in the prior art, the present invention proposes a phase change capsule with a toughened shell and a preparation method thereof. The phase change capsule is prepared by microfluidic technology, and polyvinyl alcohol is introduced into the calcium alginate shell. After repeated freezing and thawing, polyvinyl alcohol and calcium alginate cross-linked crystals are formed with polyvinyl alcohol crystals as cross-linking points, which can greatly improve the compressive strength and toughness of the phase change capsule.
[0006] Technical solution: One of the purposes of the present invention is to provide a method for preparing a phase-change capsule with a toughened shell, the steps of which are as follows:
[0007] Step 1, dissolving polyvinyl alcohol in deionized water, stirring and dissolving to form solution A, and then adding sodium alginate, stirring and dissolving to form solution B as the external phase fluid;
[0008] Step 2: Dissolve calcium chloride in deionized water until it is fully dissolved to form solution C;
[0009] Step 3: Heat the phase change material to be coated until it is melted, and add a lipophilic emulsifier as the internal phase fluid;
[0010] Step 4: Pumping the external phase fluid and the internal phase fluid into the flow focusing microfluidic chip by syringe pumps respectively, and generating a composite emulsion precursor at the outlet of the chip channel;
[0011] Step 5: Using solution C as the collection liquid, collecting the composite emulsion precursor, and achieving shell solidification through chemical reaction to complete the preparation of the phase change capsule;
[0012] Step 6: freeze-thaw the phase-change capsule prepared in step 5 three times in liquid nitrogen to obtain a phase-change capsule with a toughened shell;
[0013] In the preparation process of steps 3 to 5, the phase change material needs to be kept in a molten state, and the temperature is higher than the melting temperature of the phase change material.
[0014] Preferably, in step 1, the molecular weight of the polyvinyl alcohol is 13,000 to 23,000, and the alcoholysis degrees are 87% to 89% and 98% to 99%, respectively, and the mass ratio of the two is 1:4.5.
[0015] Preferably, in step 1, 5% polyvinyl alcohol by mass is dissolved in deionized water, and the solution A is formed after sufficient stirring and dissolution, and then sodium alginate is added, and the solution B is formed after sufficient stirring and dissolution. As the external phase fluid, the mass ratio of sodium alginate to polyvinyl alcohol is 1:2.45.
[0016] Preferably, in step 2, calcium chloride having a mass fraction of 4 to 6% is dissolved in deionized water, and solution C is formed after the calcium chloride is fully dissolved.
[0017] Furthermore, in the step 2, 5% by mass of calcium chloride is dissolved in deionized water, and after being fully dissolved, a solution C is formed.
[0018] Preferably, the phase change material in step three is paraffin.
[0019] Preferably, in step 3, the phase change material is paraffin RT25, the lipophilic emulsifier is Span 80, and the mass fraction of the lipophilic emulsifier is 1-3%; and in steps 3-5, the temperature is controlled at 28-30°C.
[0020] Furthermore, the mass fraction of the lipophilic emulsifier is 2%.
[0021] Preferably, the core glass channel portion of the flow focusing microfluidic chip in step 4 is made of an inner phase tube nested inside an outer phase tube, the inner diameter ratio of the inner phase tube to the outer phase tube is 0.46 to 0.50, and coaxial nesting must be ensured between them; the flow rate ratio of the inner phase to the outer phase fluid is 1:3.2 to 1:3.8.
[0022] Furthermore, the inner diameter ratio of the inner phase tube to the outer phase tube is 0.47, and coaxial nesting must be achieved therebetween; the flow rate ratio of the inner phase fluid to the outer phase fluid is 1:3.6.
[0023] Furthermore, in the step 5, solution C is used as the collection liquid to collect the composite emulsion precursor, specifically, the composite emulsion precursor is dropped into solution C, and the shell is solidified by chemical reaction.
[0024] Preferably, the three times of freeze-thawing with liquid nitrogen in step 6 are as follows: quick freezing with -196° C. liquid nitrogen for 0.5 h, then thawing to room temperature for 1 h, and repeating this three times.
[0025] Preferably, the step of fully stirring and dissolving to form solution A is as follows: the stirring temperature is 90 to 95° C., and the stirring is continued for 2 to 4 hours at a speed of 700 to 900 rpm with a magnetic stirrer to form solution A, and the solution is cooled to room temperature; the step of fully stirring and dissolving to form solution B is as follows: the stirring temperature is 60 to 65° C., and the stirring is continued for 1 to 3 hours at a speed of 700 to 900 rpm with a magnetic stirrer to form solution B, and the solution is cooled to room temperature.
[0026] Further, after sufficient stirring and dissolving, solution A is formed as follows: the stirring temperature is 90°C, and the stirring is continued for 3 hours at a speed of 700-900 rpm with a magnetic stirrer to form solution A, and the solution is cooled to room temperature; after sufficient stirring and dissolving, solution B is formed: the stirring temperature is 60°C, and the stirring is continued for 1 hour at a speed of 700-900 rpm with a magnetic stirrer to form solution B, and the solution is cooled to room temperature.
[0027] Another object of the present invention is to provide a phase change capsule with a toughened shell prepared based on the above method.
[0028] The phase-change capsule with a toughened shell provided by the present invention uses polyvinyl alcohol-calcium alginate as the shell material, and forms a polyvinyl alcohol-calcium alginate shell around the inner core paraffin, thereby achieving successful encapsulation of the phase-change material. The particle size range of the prepared phase-change capsule is 500μm to 700μm.
[0029] Beneficial effects: (1) The present invention adopts microfluidic technology to prepare phase change capsules, and especially introduces an appropriate amount of polyvinyl alcohol into the common calcium alginate shell, so that the network structure formed by polyvinyl alcohol and calcium alginate penetrates each other to achieve double cross-linking. On this basis, after repeated freezing and thawing, polyvinyl alcohol and calcium alginate cross-linked crystals are formed with polyvinyl alcohol crystals as cross-linking points, and the hydrogen bonds in the molecular chains of polyvinyl alcohol are weakened after forming a complex, and the network structure formed by polyvinyl alcohol and calcium alginate is enhanced in tightness. As a result, the compressive strength and toughness of the traditional calcium alginate shell are greatly improved. Compared with the conventional calcium alginate shell, the shell compression strength of the phase change capsule prepared by the present invention is enhanced by 20.5 times, and the toughness is increased by 31.18 times.
[0030] (2) The method provided by the present invention is simple in process, low in cost and environmentally friendly.
[0031] (3) The present invention adopts microfluidic technology to prepare phase change capsules, which has the advantages of good controllability, high coating success rate, and good monodispersity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the implementation mode of the present application, the drawings required for the implementation mode will be briefly introduced below. Obviously, the drawings described below are only the implementation modes recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 The present invention is a flow chart of a method for preparing a phase-change capsule with a toughened shell;
[0034] Figure 2 It is an operation flow chart of a preparation method of a phase-change capsule with a toughened shell and a finished product picture of the present invention;
[0035] Figure 3 The following are scanning electron microscope images of the surface and cross section of the phase change capsule prepared by the prior art (Comparative Example 1) and the phase change capsule with a toughened shell prepared by Example 1 of the present invention, wherein (a1) and (a2) are scanning electron microscope images of the surface of the phase change capsule with 3% calcium alginate as the shell in the prior art; (a3) is a scanning electron microscope image of the cross section of the phase change capsule with 3% calcium alginate as the shell in the prior art; (b1) and (b2) are scanning electron microscope images of the surface of the phase change capsule with a toughened shell in Example 1 of the present invention; (b3) is a scanning electron microscope image of the cross section of the phase change capsule with a toughened shell in Example 1 of the present invention;
[0036] Figure 4 It is a stress and strain comparison diagram of the phase change capsule prepared by the prior art (Comparative Example 1) and the phase change capsule with a toughened shell prepared by Example 1 of the present invention;
[0037] Figure 5 A comparison chart of the compressive strength and compressive elastic modulus of the phase change capsule prepared by the prior art (Comparative Example 1) and the phase change capsule with a toughened shell prepared by Example 1 of the present invention;
[0038] Figure 6 Comparison diagram of stress and strain of phase change capsules prepared by prior art (Comparative Example 1) and phase change capsules with toughened shells prepared by Examples 1 to 3 of the present invention;
[0039] Figure 7 Comparison diagram of stress and strain of phase change capsules (Example 1, Comparative Example 2, Comparative Example 3) with toughened shells prepared according to different freeze-thaw cycles. DETAILED DESCRIPTION
[0040] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the embodiments of the present invention are not limited thereto.
[0041] Unless otherwise specified, the reagents used in the examples of this specification can be purchased from the market.
[0042] The molecular weight of polyvinyl alcohol is 13000-23000, and the alcoholysis degree is 87%-89% and 98%-99% respectively;
[0043] The core glass channel part of the flow focusing microfluidic chip is made of an inner phase tube nested inside an outer phase tube. The inner diameter ratio of the inner phase and outer phase tubes is 0.46-0.50, and coaxial nesting must be ensured between them; the flow rate ratio of the inner phase and outer phase fluids is 1:3.2-1:3.8.
[0044] Example 1
[0045] This embodiment provides a method for preparing a phase change capsule with a toughened shell, see Figure 1 and Figure 2 , the specific steps are as follows:
[0046] (1) Weigh 1 g of polyvinyl alcohol (with a degree of alcoholysis of 87% to 89%) and 4.5 g of polyvinyl alcohol (with a degree of alcoholysis of 98% to 99%), dissolve them in 104.5 mL of deionized water at room temperature, stir mechanically at 90° C. for 3 hours, cool to room temperature after sufficient dissolution, add 2.245 g of sodium alginate, stir mechanically at 60° C. for 1 hour to dissolve, and obtain a polyvinyl alcohol aqueous solution of sodium alginate.
[0047] (2) Weigh 20 g of calcium chloride and dissolve it in 380 g of deionized water at room temperature with mechanical stirring.
[0048] (3) Weigh 1.12 g of the lipophilic emulsifier Span 80 and dissolve it in 55 g of paraffin (RT25) at 30°C.
[0049] (4) The inner phase tube (outer diameter 2.5 mm, inner diameter 1.4 mm) in the glass tube of the flow focusing microfluidic chip is coaxially inserted into another cylindrical capillary (outer diameter 4 mm, inner diameter 3 mm); the dispensing needles with an outer diameter of 1.8 mm and an inner diameter of 1.5 mm are respectively connected to the inner and outer phase tubes using 5-minute epoxy resin glue and fixed on the glass slide. This process requires that the concentricity of the inner and outer phase tubes is highly consistent, the epoxy resin glue connection is well sealed, and the dispensing needle is connected to the injection pump.
[0050] (5) Paraffin wax (RT25) and polyvinyl alcohol aqueous solution of sodium alginate were pumped into a flow focusing microfluidic chip as the inner and outer phases, respectively, using a syringe pump with a flow rate ratio of 1:3.6 to generate a composite emulsion precursor at the outlet of the chip channel.
[0051] (6) The composite emulsion precursor obtained in (5) is dripped into a calcium chloride aqueous solution to achieve shell solidification to complete the preparation of the phase change capsule.
[0052] (7) The obtained phase-change capsules were freeze-thawed by liquid nitrogen (-196°C), i.e., quick-frozen for 0.5 hour and then thawed to room temperature for 1 hour, and repeated three times.
[0053] Example 2
[0054] The same as Example 1, except that the amounts of deionized water and sodium alginate added in step (1) are different, as follows:
[0055] (1) Weigh 1 g of polyvinyl alcohol (with a degree of alcoholysis of 87% to 89%) and 4.5 g of polyvinyl alcohol (with a degree of alcoholysis of 98% to 99%), dissolve them in 177.83 mL of deionized water at room temperature, stir mechanically at 90° C. for 3 hours, cool to room temperature after sufficient dissolution, add 3.74 g of sodium alginate, stir mechanically at 60° C. for 1 hour to dissolve, and obtain a polyvinyl alcohol aqueous solution of sodium alginate.
[0056] (2) Weigh 20 g of calcium chloride and dissolve it in 380 g of deionized water at room temperature with mechanical stirring.
[0057] (3) Weigh 1.12 g of the lipophilic emulsifier Span 80 and dissolve it in 55 g of paraffin (RT25) at 30°C.
[0058] (4) The inner phase tube (outer diameter 2.5 mm, inner diameter 1.4 mm) in the glass tube of the flow focusing microfluidic chip is coaxially inserted into another cylindrical capillary (outer diameter 4 mm, inner diameter 3 mm); the dispensing needles with an outer diameter of 1.8 mm and an inner diameter of 1.5 mm are respectively connected to the inner and outer phase tubes using 5-minute epoxy resin glue and fixed on the glass slide. This process requires that the concentricity of the inner and outer phase tubes is highly consistent, the epoxy resin glue connection is well sealed, and the dispensing needle is connected to the injection pump.
[0059] (5) Paraffin wax (RT25) and polyvinyl alcohol aqueous solution of sodium alginate were pumped into a flow focusing microfluidic chip as the inner and outer phases, respectively, using a syringe pump with a flow rate ratio of 1:3.6 to generate a composite emulsion precursor at the outlet of the chip channel.
[0060] (6) The composite emulsion precursor obtained in (5) is dripped into a calcium chloride aqueous solution to achieve shell solidification to complete the preparation of the phase change capsule.
[0061] (7) The obtained phase-change capsules were freeze-thawed by liquid nitrogen (-196°C), i.e., quick-frozen for 0.5 hour and then thawed to room temperature for 1 hour, and repeated three times.
[0062] Example 3
[0063] The same as Example 1, except that the amounts of polyvinyl alcohol, deionized water and sodium alginate added in step (1) are different, as follows:
[0064] (1) Weigh 2 g of polyvinyl alcohol (with a degree of alcoholysis of 87% to 89%) and 9 g of polyvinyl alcohol (with a degree of alcoholysis of 98% to 99%), dissolve them in 126.5 mL of deionized water at room temperature, stir mechanically at 90° C. for 3 hours, cool to room temperature after sufficient dissolution, add 2.806 g of sodium alginate, stir mechanically at 60° C. for 1 hour to dissolve, and obtain a polyvinyl alcohol aqueous solution of sodium alginate.
[0065] (2) Weigh 20 g of calcium chloride and dissolve it in 380 g of deionized water at room temperature with mechanical stirring.
[0066] (3) Weigh 1.12 g of the lipophilic emulsifier Span 80 and dissolve it in 55 g of paraffin (RT25) at 30°C.
[0067] (4) The inner phase tube (outer diameter 2.5 mm, inner diameter 1.4 mm) in the glass tube of the flow focusing microfluidic chip is coaxially inserted into another cylindrical capillary (outer diameter 4 mm, inner diameter 3 mm); the dispensing needles with an outer diameter of 1.8 mm and an inner diameter of 1.5 mm are respectively connected to the inner and outer phase tubes using 5-minute epoxy resin glue and fixed on the glass slide. This process requires that the concentricity of the inner and outer phase tubes is highly consistent, the epoxy resin glue connection is well sealed, and the dispensing needle is connected to the injection pump.
[0068] (5) Paraffin wax (RT25) and polyvinyl alcohol aqueous solution of sodium alginate were pumped into a flow focusing microfluidic chip as the inner and outer phases, respectively, using a syringe pump with a flow rate ratio of 1:3.6 to generate a composite emulsion precursor at the outlet of the chip channel.
[0069] (6) The composite emulsion precursor obtained in (5) is dripped into a calcium chloride aqueous solution to achieve shell solidification to complete the preparation of the phase change capsule.
[0070] (7) The obtained phase-change capsules were freeze-thawed by liquid nitrogen (-196°C), i.e., quick-frozen for 0.5 hour and then thawed to room temperature for 1 hour, and repeated three times.
[0071] Comparative Example 1
[0072] This comparative example is a method for preparing phase change capsules in the prior art, which is as follows:
[0073] (1) Weigh 7.5 g of sodium alginate and dissolve it in 142.5 g of deionized water under mechanical stirring at 60° C. for 1 hour to obtain a sodium alginate aqueous solution.
[0074] (2) Weigh 20 g of calcium chloride and dissolve it in 380 g of deionized water at room temperature with mechanical stirring.
[0075] (3) Weigh 1.12 g of the lipophilic emulsifier Span 80 and dissolve it in 55 g of paraffin (RT25) at 30°C.
[0076] (4) The inner phase tube (outer diameter 2.5 mm, inner diameter 1.4 mm) in the glass tube of the flow focusing microfluidic chip is coaxially inserted into another cylindrical capillary (outer diameter 4 mm, inner diameter 3 mm); the dispensing needles with an outer diameter of 1.8 mm and an inner diameter of 1.5 mm are respectively connected to the inner and outer phase tubes using 5-minute epoxy resin glue and fixed on the glass slide. This process requires that the concentricity of the inner and outer phase tubes is highly consistent, the epoxy resin glue connection is well sealed, and the dispensing needle is connected to the injection pump.
[0077] (5) Paraffin wax (RT25) and sodium alginate aqueous solution were pumped into a flow focusing microfluidic chip as the inner and outer phases, respectively, using a syringe pump with a flow rate ratio of 1:3.6 to generate a composite emulsion precursor at the chip channel outlet.
[0078] (6) The composite emulsion precursor obtained in (5) is dripped into a calcium chloride aqueous solution to achieve shell solidification, thereby completing the preparation of a phase change capsule with a shell of calcium alginate.
[0079] Comparative Example 2
[0080] The same as Example 1, except that step (7) is not adopted, that is, the prepared phase change capsules are not subjected to liquid nitrogen freeze-thaw, and the obtained composite emulsion precursor is dropped into a calcium chloride aqueous solution to achieve shell solidification, thereby completing the preparation of phase change capsules with a shell of polyvinyl alcohol-calcium alginate.
[0081] Comparative Example 3
[0082] The same as Example 1, except that in step (7), the liquid nitrogen freeze-thaw process is not repeated three times but only repeated once. The obtained phase-change capsules are freeze-thawed by liquid nitrogen (-196° C.), that is, quick-frozen for 0.5 hours and then thawed to room temperature for 1 hour, and repeated once.
[0083] The products prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were analyzed.
[0084] like Figure 3 As shown, the surface of the calcium alginate phase change capsule prepared by the existing method (Comparative Example 1) is relatively smooth, and the cross-section is neatly arranged and relatively sparse. The organizational morphology of calcium alginate is linear, without interweaving, and the organizational morphology does not have a uniform network structure. The shell material of the toughened phase change capsule obtained in Example 1 is polyvinyl alcohol-calcium alginate. Compared with the existing method, the surface of the composite capsule containing polyvinyl alcohol is relatively wrinkled and rough. Figure 3 (b1)(b2)(b3) All of them show a uniformly distributed mesh-like interweaving pattern.
[0085] The compression capsule experiment was carried out using an electronic universal testing machine to compare the mechanical properties of the phase change capsule with a toughened shell (polyvinyl alcohol-calcium alginate) prepared in Example 1 and the phase change capsule with calcium alginate as the shell material prepared in Comparative Example 1. Figure 4 and Figure 5 As shown. The strain of the phase change capsule prepared in Example 1 increased from 27.57% to 80.40%, which is about 2.91 times higher than that of the calcium alginate shell, and the compressive strength increased from 0.042MPa to 0.861MPa, which is about 20.5 times higher. The compressive elastic modulus decreased from 0.97MPa to 0.48MPa due to the weakening of hydrogen bonds in the molecular chain of polyvinyl alcohol after forming a composite, but this did not affect its toughness from 0.498J / m 3 Increased to 15.526 J / m 3 , which is about 31.18 times higher. It can be seen that the preparation method provided by the present invention greatly improves the mechanical strength of the phase change capsule.
[0086] from Figure 6 It can be seen that among Examples 1-3, the product prepared in Example 1 has the best mechanical properties.
[0087] from Figure 7 It can be seen that the mechanical properties of the phase change capsules that have not been frozen and thawed by liquid nitrogen or have only been frozen and thawed once are not as good as those that have been frozen and thawed three times. This is because after repeated freezing and thawing, polyvinyl alcohol and calcium alginate cross-linked crystals are formed with polyvinyl alcohol crystals as cross-linking points, and the hydrogen bonds in the molecular chains of polyvinyl alcohol are weakened after forming a complex, and the tightness of the network structure formed by polyvinyl alcohol and calcium alginate is enhanced. As a result, the compressive strength and toughness of the traditional calcium alginate shell have been greatly improved.
[0088] The above-mentioned implementation mode is the best implementation mode of the present invention, but the preparation method of the present invention is not limited by the above-mentioned implementation mode. Any other changes, modifications, substitutions, combinations and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
[0089] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned implementation modes, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation modes of the present invention.
Claims
1. A method for preparing a phase-change capsule with a toughened shell, characterized in that: Here are the steps: Step 1, dissolving polyvinyl alcohol in deionized water, stirring and dissolving to form solution A, and then adding sodium alginate, stirring and dissolving to form solution B as the external phase fluid; Step 2: Dissolve calcium chloride in deionized water until it is fully dissolved to form solution C; Step 3: Heat the phase change material to be coated until it is melted, and add a lipophilic emulsifier as the internal phase fluid; Step 4: Pumping the external phase fluid and the internal phase fluid into the flow focusing microfluidic chip by syringe pumps respectively, and generating a composite emulsion precursor at the outlet of the chip channel; Step 5: Using solution C as the collection liquid, collecting the composite emulsion precursor, and achieving shell solidification through chemical reaction to complete the preparation of the phase change capsule; Step 6: freeze-thaw the phase-change capsule prepared in step 5 three times in liquid nitrogen to obtain a phase-change capsule with a toughened shell; In the preparation process of steps 3 to 5, the phase change material needs to be kept in a molten state, and the temperature is higher than the melting temperature of the phase change material.
2. A method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: In the step 1, the molecular weight of the polyvinyl alcohol is 13000-23000, and the alcoholysis degrees are 87%-89% and 98%-99% respectively, and the mass ratio of the two is 1:4.
5.
3. A method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: In the step 1, 5% polyvinyl alcohol by mass is dissolved in deionized water, and the solution A is formed after sufficient stirring and dissolution. Then, sodium alginate is added, and the solution B is formed after sufficient stirring and dissolution. As the external phase fluid, the mass ratio of sodium alginate to polyvinyl alcohol is 1:2.
45.
4. The method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: In the step 2, calcium chloride with a mass fraction of 4-6% is dissolved in deionized water, and after being fully dissolved, a solution C is formed.
5. The method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: In the step three, the phase change material is paraffin.
6. A method for preparing a phase-change capsule with a toughened shell according to claim 5, characterized in that: In the step 3, the phase change material is paraffin RT25, the lipophilic emulsifier is Span 80, and the mass fraction of the lipophilic emulsifier is 1-3%; In steps 3 to 5, the temperature is controlled at 28 to 30°C.
7. A method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: The core glass channel portion of the flow focusing microfluidic chip in step 4 is made of an inner phase tube nested inside an outer phase tube, the inner diameter ratio of the inner phase tube to the outer phase tube is 0.46 to 0.50, and coaxial nesting must be ensured between them; the flow rate ratio of the inner phase to the outer phase fluid is 1:3.2 to 1:3.
8.
8. The method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: The three times of freezing and thawing with liquid nitrogen in step 6 are specifically: quick freezing with -196° C. liquid nitrogen for 0.5 h, then thawing to room temperature for 1 h, and repeating this three times.
9. The method for preparing a phase-change capsule with a toughened shell according to claim 1, characterized in that: In the step 1, the solution A is formed after sufficient stirring and dissolving: the stirring temperature is 90-95° C., and the stirring is continued for 2-4 hours at a speed of 700-900 rpm with a magnetic stirrer to form solution A, and the solution is cooled to room temperature; the solution B is formed after sufficient stirring and dissolving: the stirring temperature is 60-65° C., and the stirring is continued for 1-3 hours at a speed of 700-900 rpm with a magnetic stirrer to form solution B, and the solution is cooled to room temperature.
10. A phase change capsule with a toughened shell prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Phase-change temperature-regulating chitosan composite fiber and preparation method thereof
CN105887241A
Long-acting antibacterial hydrogel and preparation method thereof
CN107335091A
Method for finishing fabric by microcapsules
CN109468851A
Phase-change nano-biochar composite material for asphalt pavement temperature control and preparation method of phase-change nano-biochar composite material
CN118459144A
A method for capsulating useful agricultural culture using alginate shell bead having improved drought resistance viability of useful agricultural culture
KR100864399B1